Electrophotographic belt and electrophotographic image forming apparatus

The electrophotographic belt addresses the issue of wear and cracks on intermediate transfer belts by using a cross-linked polyester urethane conductive layer with a triazine ring, achieving improved durability and image quality.

JP2025043155APending Publication Date: 2025-03-28CANON KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023150497
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The inner peripheral surface of intermediate transfer belts in electrophotographic devices experiences wear and cracks due to long-term use, leading to reduced durability and quality of electrophotographic images.

Method used

An electrophotographic belt with a substrate made of crystalline polyester and a conductive layer comprising cross-linked polyester urethane with a triazine ring, where the nanoindentation hardness coefficient of variation is maintained at 0.25 or less across specific observation regions.

Benefits of technology

The solution provides enhanced wear resistance and crack resistance for the conductive layer, ensuring stable high-quality electrophotographic image formation even after long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043155000001_ABST
    Figure 2025043155000001_ABST
Patent Text Reader

Abstract

To provide an electrophotographic belt that comprises a resin layer having an inner peripheral surface in which wear and cracks hardly occur even if it is used for a long period.SOLUTION: An electrophotographic belt 100 has a base layer 101 that has an endless shape, and a conductive layer 102 that is in contact with the base layer. The base layer includes crystalline polyester. The conductive layer includes cross-linked polyester urethane. When eight 2.5×2.5 mm square observation areas are placed in a circumferential direction of the electrophotographic belt, in at least six observation areas of the eight observation areas, the coefficient of variation of nano-indentation hardness is 0.25 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrophotographic belt and an electrophotographic image forming apparatus including the electrophotographic belt. [Background technology]

[0002] In an electrophotographic image forming apparatus (hereinafter also referred to as an "electrophotographic apparatus"), an electrostatic image carrier such as a photosensitive drum is charged, and the charged electrostatic image carrier is exposed to light to form an electrostatic latent image. The electrostatic latent image is then developed with frictionally charged toner, and the toner image is transferred and fixed to a recording medium such as paper, thereby forming a desired image on the recording medium. As a transfer method for electrophotographic devices, an intermediate transfer method is known in which an unfixed toner image on an electrostatic charge carrier such as a photosensitive drum is primarily transferred to an intermediate transfer body by a current supplied from a transfer power source, and then the unfixed toner image is secondarily transferred from the intermediate transfer body to a recording medium. A transfer power source is provided for each of the primary transfer and secondary transfer, and the current value is controlled to be optimal according to the surrounding environment (temperature and humidity) and the type of recording medium. Such an intermediate transfer method is particularly adopted in color electrophotographic devices.

[0003] In color electrophotographic devices, toner of four colors (yellow, magenta, cyan, and black) is transferred sequentially from the image forming section of each color onto an intermediate transfer body, and the resulting composite image is then transferred all at once onto a recording medium, resulting in advantages such as faster printing and higher quality images. In recent years, with the increasing need for miniaturization and cost reduction of copiers and printers, reduction in the number of parts has been considered. Specifically, as described in Patent Document 1, an intermediate transfer belt has been proposed that has a base layer containing an endless crystalline polyester and a conductive layer formed on its inner peripheral surface. Patent Document 1 lists a problem that occurs when a large amount of electronic conductive agent is contained in the conductive layer to increase the conductivity of the conductive layer, resulting in a decrease in adhesion between the conductive layer and the base layer. Patent Document 1 also discloses that the above problem can be solved by containing a polyester resin having two monomer units derived from fumaric acid in the conductive layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-190720 A [Patent Document 2] Japanese Patent Application Publication No. 09-211934 Summary of the Invention [Problem to be solved by the invention]

[0005] The inner peripheral surface of the intermediate transfer belt is required to have high durability because a roller for rotating the intermediate transfer belt contacts the inner peripheral surface. Specifically, for example, even when the belt is used for forming electrophotographic images for a long period of time, the conductive layer is required to be free from wear and cracks. According to the study by the present inventors, the electrophotographic belt according to Patent Document 1 is recognized to require further improvement in durability for use over a longer period of time. Here, Patent Document 2 discloses that the hardness is increased by crosslinking the polyester resin with a melamine crosslinking agent. Therefore, the present inventors attempted to crosslink the polyester in the conductive layer with a melamine crosslinking agent in order to further improve the abrasion resistance of the conductive layer. However, when the obtained electrophotographic belt was used to form an electrophotographic image, cracks were generated in the resin layer relatively early.

[0006] At least one embodiment of the present disclosure is a method for preventing wear and cracks from occurring on the inner circumferential surface even with long-term use. The present disclosure is directed to providing an electrophotographic belt having a resin layer that is resistant to adhesion to the toner particles. Also, at least one aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus that can stably form high-quality electrophotographic images. [Means for solving the problem]

[0007] According to at least one aspect of the present disclosure, there is provided an electrophotographic belt having an endless shape, comprising: The electrophotographic belt has a substrate having an endless shape and a conductive layer in contact with the substrate, The base layer comprises a crystalline polyester, the conductive layer comprises a cross-linked polyester urethane; The crosslinked polyester urethane has a triazine ring in the molecule, When the length in the width direction perpendicular to the circumferential direction of the electrophotographic belt is W, and a region of W / 4 from the midpoint in the width direction toward both ends in the width direction is defined as a central region, In the central region of the outer surface of the conductive layer opposite to the surface facing the base layer, eight square observation regions, each having a side length of 2.5 mm, are placed in the circumferential direction of the electrophotographic belt such that one side of the square is parallel to the width direction, and at least six of the eight observation regions satisfy the following condition. <Condition> The observation area is equally divided by four lines parallel to one side of the observation area and four lines perpendicular to the first lines, and the coefficient of variation of nanoindentation hardness measured at 16 intersections of these lines in an environment of 25°C is 0.25 or less.

[0008] According to at least one aspect of the present disclosure, there is provided an electrophotographic image forming apparatus including the electrophotographic belt as an intermediate transfer belt. Effect of the Invention

[0009] According to at least one aspect of the present disclosure, it is possible to obtain an electrophotographic belt having a resin layer on an inner circumferential surface of which wear and cracks are unlikely to occur even after long-term use. According to at least one aspect of the present disclosure, it is possible to obtain an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic diagram of an electrophotographic belt according to the present disclosure. [Diagram 2] 1 is a schematic diagram of an electrophotographic imaging apparatus according to the present disclosure; [Diagram 3] FIG. 4 is an explanatory diagram of the arrangement position of an observation region of a conductive layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In the present disclosure, the description of "XX or more and YY or less" or "XX to YY" expressing a numerical range means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. In addition, when a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In the present disclosure, for example, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ. In addition, in the present disclosure, the unit of surface resistivity "Ω / □" means "Ω / square".

[0012] As described above, the present inventors have attempted to crosslink the polyester in the conductive layer with a melamine crosslinking agent in order to improve the abrasion resistance of the conductive layer. However, when the obtained electrophotographic belt was used to form an electrophotographic image, cracks were generated in the resin layer relatively early. In addition, when a biaxially stretched cylindrical film was used as the base layer, the occurrence of cracks was more prominent. Therefore, the present inventors investigated the cause of the cracks. As a result, they speculated that the cracks were caused by the following mechanism.

[0013] That is, the conductive layer of the electrophotographic belt obtained above is a cured film of a coating film of a coating material for forming a conductive layer containing polyester urethane and a melamine crosslinking agent (hereinafter, sometimes simply referred to as "coating material") formed on the inner peripheral surface of a base layer containing a crystalline polyester. When forming such a cured film, it is necessary to heat the coating film to a temperature of 150°C or higher in order to promote the reaction between the polyester urethane and the melamine crosslinking agent in the coating film. Such a temperature exceeds the glass transition temperature of the crystalline polyester in the base layer. Therefore, the base layer shrinks due to the heat required for curing the coating film (forming the conductive layer). Then, during the curing process, the coating film shrinks in accordance with the shrinkage of the base layer while curing. Therefore, the obtained conductive layer has relatively high density parts and low density parts inside.

[0014] The high density area has a high hardness, and the low density area has a low hardness, so that the conductive layer has uneven hardness. When an electrophotographic belt having such a conductive layer is mounted in an electrophotographic device and rotated, stress is concentrated in the area of ​​the conductive layer with low hardness, which may cause cracks. In addition, the biaxially stretched cylindrical film shrinks more when heated. Therefore, when a biaxially stretched cylindrical film is used as the base layer, the occurrence of cracks is more noticeable. Based on these considerations, the present inventors have come to the realization that in order to achieve high levels of both abrasion resistance and crack resistance in the conductive layer when an electrophotographic belt is used over a long period of time, it is essential to suppress unevenness in the hardness of the conductive layer, which is a hardened coating of a paint film containing polyester urethane and a melamine crosslinking agent.

[0015] Based on this understanding, the present inventors have conducted further studies and have found that an electrophotographic belt having the following configuration achieves both high levels of wear resistance and crack resistance. That is, the electrophotographic belt according to one embodiment of the present disclosure has a base layer having an endless shape and a conductive layer in contact with the base layer. The base layer contains a crystalline polyester, and the conductive layer contains a cross-linked polyester urethane, which has a triazine ring in its molecule. When the length in the width direction perpendicular to the circumferential direction of the electrophotographic belt is W, and a region of W / 4 from the midpoint in the width direction to both ends in the width direction is defined as a central region, eight square observation regions, each having a side length of 2.5 mm, are placed in the circumferential direction of the electrophotographic belt in the central region on the outer surface opposite to the surface of the conductive layer facing the base layer, with one side of the square being parallel to the width direction. At least six of the eight observation regions satisfy the following condition. <Condition> The square region is equally divided by four lines parallel to one side and four lines perpendicular to the first lines, and the coefficient of variation of nanoindentation hardness measured at 16 intersections of these lines in an environment of 25°C is 0.25 or less.

[0016] When the nanoindentation hardness is measured at intervals of 0.5 mm in a square observation area of ​​2.5 μm on each side placed on the outer surface of the conductive layer, the coefficient of variation is 0.25 or less, so that stress concentration points that are the starting points of cracks are unlikely to occur in the observation area. When eight of the above observation areas are placed in the central area of ​​the outer surface of the conductive layer in the circumferential direction of the electrophotographic belt so as not to overlap each other, at least six, preferably at least seven, and more preferably eight of the eight observation areas satisfy the above condition, stress concentration points that are the starting points of cracks are unlikely to occur in the conductive layer, and cracks can be prevented from occurring in the conductive layer even after long-term use.

[0017] The positions of the eight observation regions in the central region of the outer surface of the conductive layer are not particularly limited as long as they are in the circumferential direction of the electrophotographic belt and do not overlap each other. Assuming that the cross section parallel to the circumferential direction of the electrophotographic belt is a perfect circle, it is preferable to uniformly arrange the observation regions at points O2 at 45 degrees, O3 at 90 degrees, O4 at 135 degrees, O5 at 180 degrees, O6 at 225 degrees, O7 at 270 degrees, and O8 at 315 degrees clockwise from point O1 as shown in Fig. 3. This is because it is possible to grasp the presence or absence of hardness unevenness in the entire circumferential direction of the electrophotographic belt.

[0018] The means for making the coefficient of variation of the nanoindentation hardness of the conductive layer fall within the above range is not particularly limited, but the present inventors have found that, for example, when crosslinking the melamine crosslinking agent and the polyester urethane, the shrinkage of the base layer can be easily suppressed by applying pressure at the same time as heating. This makes it possible to suppress the shrinkage of the conductive layer, making it easier to make the coefficient of variation of the nanoindentation hardness fall within the above range, and making it difficult for density differences to occur in the conductive layer formed on the base layer, thereby suppressing unevenness in the hardness of the conductive layer.

[0019] The present inventors consider the reason for this as follows. When heated to a temperature equal to or higher than the glass transition temperature, the crystalline polyester undergoes crystallization and shrinks. On the other hand, when heated under pressure, the amorphous molecules of the crystalline polyester are stretched, so the base layer hardly shrinks. Therefore, the conductive layer does not shrink either, making it easier to keep the coefficient of variation of the nanoindentation hardness within the above range, and hardness unevenness can be suppressed.

[0020] The variation coefficient of the nanoindentation hardness is preferably 0.20 or less, more preferably 0.19 or less. The lower limit is not particularly limited, but is, for example, 0.00 or more. The preferred range of the variation coefficient of the nanoindentation hardness is, for example, 0.00 to 0.20, particularly 0.07 to 0.19. As described above, the variation coefficient of the nanoindentation hardness can be reduced by suppressing the shrinkage of the base layer due to heat during the curing process of the coating film of the paint for forming the conductive layer, specifically, for example, by applying pressure to the base layer during the formation process of the conductive layer to suppress the shrinkage of the base layer.

[0021] In measuring the nanoindentation hardness, it is preferable to use a Berkovich type indenter and use a measured value in a region of 2 to 10% in the thickness (film thickness) direction from the outermost surface of the conductive layer, i.e., the surface of the conductive layer opposite to the surface facing the base layer. The region of 2 to 10% of the film thickness of the conductive layer near the outermost surface is less susceptible to the influence of the measurement environment, such as the vibration of the indenter. In addition, it is less susceptible to the influence of the base layer, so the hardness of the conductive layer itself can be evaluated more accurately.

[0022] Hereinafter, an embodiment of the electrophotographic belt according to the present disclosure will be described in detail, however, the present disclosure is not limited to the following embodiment.

[0023] <Electrophotographic belt> The electrophotographic belt according to this embodiment will be described in detail below. FIG. 1A is a perspective view of an electrophotographic belt having an endless shape. FIG. 1B is an enlarged view of an axial cross section (cross section cut at (b)) of FIG. 1A. The electrophotographic belt 100 shown in FIGS. 1A and 1B has a laminate of a base layer 101 and a conductive layer 102. The conductive layer 102 exists on the inner peripheral surface side of the base layer 101, and the conductive layer 102 is exposed to the inner peripheral surface of the electrophotographic belt. Although not shown, a surface layer (outermost layer) that comes into contact with a photosensitive drum or other members may be provided on the outer peripheral surface of the base layer 101. When the electrophotographic belt is an intermediate transfer belt, the conductive layer 102 exists on the inner peripheral surface side of the base layer 101, so that the number of transfer power sources can be reduced as described later.

[0024] 1A and 1B, a member is placed in contact with the conductive layer 102. By connecting a voltage maintaining element such as a Zener diode, it is possible to keep the potential of the conductive layer constant. As a result, a desired current can be applied to all the photosensitive drums via the conductive layer, and the electrophotographic belt can be used in an image forming apparatus capable of primary transfer as well as secondary transfer with one transfer power source.

[0025] The electrophotographic belt has an endless belt shape. The electrophotographic belt can be used by stretching it over a plurality of rollers. The endless belt shape refers to a shape obtained by joining a sheet or film-shaped molded product into a cylindrical shape, and refers to a shape that can be stretched and rotated over a plurality of rollers. Among the endless belt shapes, a seamless shape without a joint (seam) is preferred from the viewpoint of reducing unevenness in the thickness of the belt.

[0026] The electrophotographic belt has a volume resistivity of 1×10 or less when measured in a normal temperature and humidity environment (temperature 23° C., humidity 50%) in order to be used in the above-mentioned compact and low-cost image forming apparatus. 8 ~1×10 11 It is preferably in the range of Ω·cm.

[0027] In addition, the surface resistivity of the inner peripheral surface side is smaller than that of the outer peripheral surface side, and the surface resistivity measured from the inner peripheral surface side is 1.0×10 7 It is preferable that the surface resistivity of the electrophotographic belt is in the range of Ω / □ or less. If the surface resistivity is high, the transfer voltage required for the primary transfer of the toner image on the photosensitive drum to the transfer belt may be insufficient, which may result in image defects such as transfer defects.

[0028] Next, the materials constituting each layer of the electrophotographic belt and the method of forming the same will be described in detail, although the method of producing the electrophotographic belt is not particularly limited.

[0029] (base material) The endless base layer according to one embodiment of the present disclosure includes a crystalline polyester, and preferably includes a crystalline polyester and a conductive agent. If necessary, additives such as a plasticizer, an antioxidant, a decomposition inhibitor, a roughness adjuster, a filler, and an elastomer can be added. First, the crystalline polyester will be described.

[0030] The crystalline polyester as a raw material can be obtained by a polycondensation product of dicarboxylic acid and diol, a polycondensation product of oxycarboxylic acid or lactone, or a polycondensation product using a plurality of these components. An additional multifunctional monomer may be used in combination. The crystalline polyester may be a homopolyester containing one type of ester bond, or a copolyester (copolymer) containing a plurality of ester bonds. As the crystalline polyester, a crystalline polyester having an aromatic ring in the molecule, which may have higher crystallinity, can be preferably used.

[0031] As the crystalline polyester, at least one crystalline polyester selected from the group consisting of polyalkylene terephthalate and polyalkylene naphthalate, which have high crystallinity and excellent heat resistance; copolymers of polyalkylene terephthalate and polyalkylene naphthalate, copolymers of polyalkylene naphthalate and polyalkylene isophthalate; and polyesters in which some blocks of these are modified with other blocks, is preferred. At least one crystalline polyester selected from the group consisting of polyalkylene terephthalate and polyalkylene naphthalate is more preferred. Such polyesters are more likely to achieve low cost.

[0032] The number of carbon atoms of the alkylene in the polyalkylene terephthalate, polyalkylene naphthalate, and polyalkylene isophthalate is preferably 2 to 16 (more preferably 2 to 4) from the viewpoint of obtaining high crystallinity and heat resistance. More specifically, the crystalline polyester is polyethylene terephthalate, polyethylene naphthalate, or polyethylene At least one crystalline polyester selected from the group consisting of polyethylene terephthalate, polyethylene naphthalate, and modified polyethylene isophthalate, in which a part of the blocks of these polyesters are modified with other blocks, is preferred. The crystalline polyester more preferably contains at least one selected from the group consisting of polyethylene terephthalate and polyethylene naphthalate, and further preferably contains polyethylene naphthalate.

[0033] The other block may be a monomer unit of at least one compound selected from the group consisting of 1,4-naphthalenedicarboxylic acid and 2,3-naphthalenedicarboxylic acid. One of these may be used alone, or two or more may be used in combination. It may be a blend or alloy, and other resins may be added.

[0034] Next, the conductive agent will be described. The base layer may contain an ionic conductive agent as the conductive agent. The ionic conductive agent may be at least one selected from the group consisting of low molecular weight ionic conductive agents such as ionic liquids and high molecular weight ionic conductive agents such as polyether ester amides. The ionic conductive agent preferably contains an ionic liquid and a polyether ester amide.

[0035] An ionic liquid is a salt consisting of only cations and anions, and generally exists in a liquid state at room temperature. The cations that can be used include alkali metal cations, imidazolium cations, alkylammonium cations, alkylphosphonium cations, and their derivatives. As the anion, a sulfonate ion, a carboxylate ion, a phosphinate ion, etc. can be used. In addition, F - , Cl - , Br - , I - , AlCl4 - , N(CN)2 - etc.

[0036] Examples of polyether ester amides include compounds whose main component is a copolymer consisting of polyamide block units, such as nylon 6, nylon 66, nylon 11, and nylon 12, and polyether ester units. Examples of the polyether ester amides include copolymers derived from lactam or aminocarboxylate salts, polyethylene glycol, and dicarboxylic acids, such as terephthalic acid and isophthalic acid.

[0037] (Method of forming base layer) The base layer can be formed, for example, by the following method. For example, it can be formed by the method described in JP-A-2010-054942. First, a crystalline polyester, a conductive agent, and, if necessary, additives are mixed and melt-kneaded (for example, at 190 to 270°C, for example, for 3 to 5 minutes) using a kneading device or the like to prepare a conductive resin composition. Next, a preform of the conductive resin composition having a test tube shape is prepared by injection molding. The preform is stretch-blow molded in its longitudinal and circumferential directions to obtain a blown bottle of the conductive resin composition. A conductive film (biaxially stretched cylindrical film) having an endless shape stretched in the circumferential and longitudinal directions can be obtained from the blown bottle.

[0038] The base layer preferably has a biaxially stretched cylindrical film. In the biaxially stretched cylindrical film, the crystalline polyester is stretched in the longitudinal direction and the circumferential direction of the preform, so that the crystals are oriented in each direction, and the film has excellent strength. The tensile modulus of elasticity Ep in the circumferential direction and the tensile modulus of elasticity Ea in the direction perpendicular to the circumferential direction of the cylindrical film are preferably both 1000 MPa or more.

[0039] The electrophotographic belt is rotated by a plurality of rollers at a predetermined tension in the electrophotographic image forming apparatus. The electrophotographic belt is stretched by the tension, but by setting Ep to 1000 MPa or more, elongation and breakage can be prevented. In addition, by applying a predetermined tension in the circumferential direction, a compressive force is applied in a direction perpendicular to the circumferential direction of the electrophotographic belt. However, by setting Ea to 1000 MPa or more, it is possible to more reliably prevent the outer surface of the electrophotographic belt from being wrinkled in the circumferential direction due to the compressive force.

[0040] The above-mentioned tensile modulus can be controlled by the degree of orientation of the crystalline polyester in the circumferential direction of the cylindrical film and in the direction perpendicular to the circumferential direction. The degree of orientation of the crystalline polyester can be expressed by the shrinkage rate αp in the circumferential direction of the cylindrical film and the shrinkage rate αa in the direction perpendicular to the circumferential direction (axial direction) of the cylindrical film. It is preferable that the αp and αa of the cylindrical film are both 2.0% or more. A cylindrical film having αp and αa of 2.0% or more means that the crystalline polyester is sufficiently oriented in the circumferential direction and in the direction perpendicular to the circumferential direction, and when the belt is stretched, the deformation of the belt can be suppressed by the action of the shrinkage stress. A cylindrical film having such a shrinkage rate can have the above-mentioned tensile modulus Ep and Ea of 1000 MPa or more.

[0041] In addition, αp and αa can be obtained by, for example, using a thermomechanical analyzer, heating a sample piece cut out from an electrophotographic belt to a temperature 10°C higher than the glass transition temperature of the conductive resin composition (crystalline polyester) used in the base layer at a rate of 5°C / min, holding the temperature for 30 minutes, and then lowering the temperature to 25°C at a rate of 5°C / min to measure the shrinkage. The shrinkage αp is preferably 2.0 to 10.0%, more preferably 3.0 to 8.0%, and even more preferably 3.5 to 7.0%. The shrinkage αa is preferably 2.0 to 10.0%, more preferably 3.0 to 8.0%, and even more preferably 3.5 to 7.2%. Furthermore, the conductive resin composition can be melt-extruded and processed into a film or seamless belt to obtain a conductive film.

[0042] However, the thickness of the base layer is preferably 30 μm to 500 μm from the viewpoint of ensuring flexibility since the base layer is disposed in a bent state inside an electrophotographic image forming apparatus, and more preferably 40 to 100 μm. The content of the conductive agent in the base layer is preferably 1 to 40 parts by mass, and more preferably 10 to 20 parts by mass, based on 100 parts by mass of the crystalline polyester.

[0043] (Conductive layer) The conductive layer includes a crosslinked polyester urethane having a triazine ring structure in the molecule. The conductive layer is preferably a cured product of the conductive layer-forming paint. First, the conductive layer-forming paint will be described. The conductive layer-forming paint includes a polyester urethane and a melamine crosslinking agent, and if necessary, a conductive agent such as conductive particles. In addition, if necessary, additives such as a catalyst, a plasticizer, a leveling agent, a decomposition inhibitor, a roughness adjusting agent, and a filler can be added.

[0044] 1. Polyester urethane Polyester urethane can be obtained, for example, by reacting a polyester polyol having an ester bond in the molecule and hydroxyl groups at both ends of the molecule with a diisocyanate. The polyester polyol can be obtained by polycondensation of a dicarboxylic acid and a diol, polycondensation of an oxycarboxylic acid or a lactone, or polycondensation using a plurality of these components to give a hydroxyl group to the terminal. The polyester polyol preferably has an aromatic group. Diisocyanates are compounds in which two isocyanate groups are bonded to an aliphatic or aromatic compound. Examples of compounds in which an isocyanate group is bonded to a linear aliphatic compound include hexamethylene diisocyanate. Examples of compounds in which an isocyanate group is bonded to an aromatic compound include Examples of the polyester urethane include 1,3-Bis(isocyanatomethyl)benzene, etc. Commercially available polyester urethanes may be used, for example, Byron UR-1400 (product name) manufactured by Toyobo Co., Ltd.

[0045] 2. Melamine crosslinker The crosslinked polyester urethane has a triazine ring structure in the molecule. The crosslinked polyester urethane has a structure in which, for example, a melamine crosslinking agent and a polyester urethane are crosslinked, and the melamine crosslinking agent can correspond to the triazine ring structure.

[0046] Melamine crosslinking agents are obtained by alkoxylating methylolmelamine, which is produced by polycondensing melamine and formaldehyde, with an alcohol having 1 to 4 carbon atoms. The structural formula of melamine is shown in formula (A) below. Melamine has a structure in which NH2 is bonded to a triazine ring, and some or all of the six hydrogen atoms at the ends react with formaldehyde. In order for it to function as a crosslinking agent, two or more hydrogen atoms must react. The structural formula when all hydrogen atoms have reacted is shown in formula (B) below.

[0047] Furthermore, by modifying some or all of the methylol groups at the ends of methylol melamine with alcohol, a structure is formed in which alkyl groups are bonded to the ends. The following formula (C) shows a structure in which all of the methylol groups have been modified with methanol. It is possible to modify the methylol groups with alcohol, but with alcohols having long carbon chains, the crosslinking reaction is difficult to proceed due to steric hindrance. For this reason, alcohols having 1 to 4 carbon atoms are preferred.

[0048] In order to function as a crosslinking agent, two or more methylol groups must be modified. Various physical properties of the melamine crosslinking agent change depending on the degree of methylolation and the degree of alkoxylation. An appropriate melamine crosslinking agent may be selected according to the desired physical properties, but there is no particular restriction from the viewpoint of abrasion resistance, and it is sufficient that there are two or more alkoxy groups reacting with polyester urethane in the melamine crosslinking agent molecule. For example, the melamine crosslinking agent may be an alkylated melamine crosslinking agent, a methylol group type melamine crosslinking agent, an imino group type melamine crosslinking agent, a methylol / imino group type melamine crosslinking agent, or a long-chain alkylated melamine crosslinking agent.

[0049] Crosslinking proceeds by reacting alkoxylated melamine with polyester urethane. The bond between alkoxylated melamine and polyester urethane has a structure as shown in formula (D) below. However, formula (D) below shows the structure when three out of six methoxy groups have reacted.

[0050] [ka] [ka]

[0051] The crosslinked polyester urethane preferably has at least a structure represented by the following formula (1): The following structure represents a triazine ring structure in the molecule: Therefore, the melamine crosslinking agent is preferably a crosslinking agent capable of forming the structure represented by the following formula (1) by reaction with the polyester urethane. [ka]

[0052] In formula (1), R1 to R6 each independently represent is any one selected from the group consisting of a hydrogen atom, -CHOH, -CHOR, and -CHO-, provided that at least two of R to R are -CHO-; R7 is a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms (preferably 1 or 2, more preferably 1). The symbol "*" indicates a bond to a nitrogen atom that does not constitute a triazine ring in formula (1). The symbol "**" indicates a bond between the polyesterurethane and the crosslinked polyesterurethane, the bond being a bond between the polyesterurethane and a molecular chain that constitutes at least a part of the polyesterurethane.

[0053] In the structure represented by formula (1), At least one selected from the group consisting of R1 and R2; At least one selected from the group consisting of R3 and R4; *-CH2O-** is preferred. In addition, in the structure represented by formula (1), At least one selected from the group consisting of R1 and R2; At least one selected from the group consisting of R3 and R4; At least one selected from the group consisting of R5 and R6; It is more preferable that the compound is *-CH2O-**. *-CH2O-** forms a sufficient cross-linking structure, which can further improve abrasion resistance.

[0054] The content of the melamine crosslinking agent in the conductive layer-forming coating material is preferably from 10 to 60 parts by mass, and more preferably from 30 to 55 parts by mass, based on 100 parts by mass of the polyester urethane. The content of the structure represented by formula (1) in the crosslinked polyester urethane is preferably 7 to 40 mass %, more preferably 20 to 35 mass %. When the content is within the above range, a sufficient crosslinked structure is formed, and the abrasion resistance can be further improved.

[0055] 3.Conductive agent The conductive layer may include a conductive agent. The conductive agent preferably includes conductive particles. As the particles, an electronic conductive agent can be used. The electronic conductive agent includes at least one selected from the group consisting of, for example, carbon black, graphite, carbon nanotubes, carbon microcoils, graphene, zinc oxide, zinc antimonate, tin oxide, ITO (tin-doped indium oxide), and ATO (antimony-doped tin oxide). Among these, from the viewpoint of electrical conductivity, it is preferable that the conductive layer includes carbon black. In addition, a dispersant may be used to increase the dispersion stability of the carbon black in the paint.

[0056] The conductive layer forming coating material is preferably prepared by dissolving or dispersing the polyester urethane, the melamine crosslinking agent, and the conductive agent in at least one organic solvent selected from the group consisting of methyl ethyl ketone, isobutanol, methyl isobutyl ketone, toluene, and the like.

[0057] (Formation of conductive layer) The conductive layer is formed by applying the prepared conductive layer-forming paint to the inner peripheral surface of the endless belt-like base layer. Examples of the application method include spray coating, dip coating, ring coating, roll coating, etc. Then, the solvent is removed by drying, and the conductive layer can be formed as a coating film.

[0058] After drying, a crosslinking process is carried out to crosslink the polyester urethane and the melamine crosslinking agent in the conductive layer. In the crosslinking process, for example, heating is performed at 150 to 190°C for 10 seconds to 10 minutes (preferably 30 to 120 seconds). In the crosslinking process, it is preferable to apply pressure simultaneously with heating. As described above, the application of pressure suppresses the shrinkage of the base layer containing the crystalline polyester, making it easier to control the variation coefficient of nanoindentation hardness within the above range.

[0059] The method and conditions of pressurization may be any known method that can stretch the amorphous molecules of the crystalline polyester and suppress shrinkage. For example, pressurization with air is preferred. When the base layer is subjected to stretch blow molding, a method of applying air pressure to the inside of a blow bottle in which the base layer is formed can be mentioned. The pressure is preferably 0.05 to 0.3 MPa, more preferably 0.08 to 0.2 MPa, in terms of gauge pressure.

[0060] The conductive layer can be formed, for example, by the following method. A conductive layer forming paint is applied to the inside of the blown bottle obtained by the above-mentioned method for forming the base layer, and then dried. The drying method is not particularly limited, but it is preferable to dry by heating (for example, 50 to 100°C, 1 to 10 minutes). After drying, a crosslinking step is performed in which air pressure is applied and heating is performed under the above-mentioned conditions to the inside of the blown bottle on which the conductive layer has been formed, to form a conductive layer.

[0061] The surface resistivity of the outermost surface of the conductive layer, i.e., the surface opposite to the surface of the conductive layer facing the base layer, when 10 V is applied is 1.0×10 7 Ω / □ or less is preferable, and 1.0×10 6 The surface resistivity is Ω / □ or less. The lower limit of the surface resistivity is not particularly limited. When the surface resistivity is within the range, a primary transfer current equivalent to that of a conventional primary transfer having multiple transfer power sources can be supplied to each photosensitive drum.

[0062] From the viewpoint of flex resistance, the thickness of the conductive layer is preferably 0.05 μm to 10 μm, more preferably 0.1 μm to 5 μm, and even more preferably 0.5 μm to 2 μm. In consideration of the above thickness, the polyester urethane is preferably one that can be dissolved in a solvent to form a thin layer containing polyester urethane or a thin layer containing polyester urethane raw material.

[0063] The arithmetic mean value of the nanoindentation hardness in the observation region having the largest coefficient of variation among the eight observation regions described above is preferably 0.15 to 0.30 GPa, and more preferably 0.21 to 0.29 GPa. The standard deviation of the nanoindentation hardness in the observation region with the largest coefficient of variation among the eight observation regions is preferably 0.00 to 0.08 GPa, and more preferably 0.00 to 0.05 GPa. The coefficient of variation in the observation region having the largest coefficient of variation among the eight observation regions is preferably 0.00 to 0.20, and more preferably 0.00 to 0.19. When the arithmetic mean value, standard deviation, and coefficient of variation are within the above ranges, cracks are more easily suppressed.

[0064] Furthermore, the arithmetic mean value of the nanoindentation hardness, that is, the arithmetic mean value of 128 points measured from eight observation regions, is preferably 0.15 to 0.50 GPa, more preferably 0.15 to 0.30 GPa, and further preferably 0.21 to 0.30 GPa. By making the average nanoindentation hardness 0.15 GPa or more, it is possible to further suppress the occurrence of physical deterioration such as wear and tear due to friction with other sliding members (e.g., transfer rollers) mounted on electrophotographic devices. There is no particular upper limit to the average nanoindentation hardness, but a hardness of 0.50 GPa or less makes it easier to suppress physical damage to sliding members mounted on general electrophotographic devices.

[0065] The nanoindentation hardness can be adjusted, for example, by the degree of crosslinking of the polyester urethane (before melamine crosslinking) or the degree of melamine crosslinking of the crosslinked polyester urethane. Specifically, for example, a polyfunctional isocyanate compound such as polymeric MDI is used as an isocyanate compound as a raw material of the polyester urethane, thereby introducing a three-dimensional crosslinking structure into the polyester urethane, thereby increasing the nanoindentation hardness of the conductive layer. In addition, the nanoindentation hardness of the conductive layer can be increased by increasing the blending ratio of the melamine crosslinking agent used in the production of the crosslinked polyester urethane to the polyester urethane. The standard deviation of the nanoindentation hardness is, for example, preferably 0.00 to 0.08, and more preferably 0.00 to 0.05.

[0066] (Surface layer (outermost layer)) A surface layer (outermost layer) that comes into contact with the photosensitive drum or other members may be provided on the outer peripheral surface of the base layer. An example of the surface layer is a layer that contains a cured product of an active energy ray curable resin and has excellent abrasion resistance. Such a surface layer can be provided, for example, by applying a composition containing an active energy ray curable resin such as a photocurable resin onto the outer peripheral surface of the base layer and curing it. An example of the active energy ray curable resin is preferably an acrylic resin. In addition, conductive particles may be added to adjust the surface resistivity of the surface layer. Examples of the conductive particles include carbon black, graphite, carbon nanotubes, carbon microcoils, zinc oxide, and zinc antimonate.

[0067] The electrophotographic belt has an endless configuration. The application of the electrophotographic belt according to the present disclosure is not limited to an intermediate transfer belt, and it may also be suitably used as, for example, a transport transfer belt, etc. The electrophotographic belt may be an intermediate transfer belt or a transport transfer belt.

[0068] <Electrophotographic image forming apparatus> The electrophotographic image forming apparatus according to the present disclosure will be described in more detail with reference to Figures 2A and 2B. The electrophotographic image forming apparatus includes image forming units 205a, 205b, 205c, 205d, 205a forming yellow images, 205a forming magenta images, 205c forming cyan images, and 205d forming black images. The image forming unit 205a will be described in detail below as an example.

[0069] 2B is an enlarged schematic diagram of the image forming unit 205a. The image forming unit 205a has a photosensitive drum 206a, which is an image carrier, and is rotated at a predetermined process speed. Around the photosensitive drum 206a, a charging roller 207a, which is a charging member, a developing member 209a containing toner 208a, and a drum cleaning member 210a are provided. Furthermore, around the photosensitive drum 206a, an exposure member 211a is provided between the charging roller 207a and the developing member 209a.

[0070] The surface of the photosensitive drum 206a is charged by a charging roller 207a, and the charged electrostatic image carrier is exposed by an exposure member 211a to form an electrostatic latent image (toner image). The electrostatic latent image is then developed by a frictionally charged toner 208a in a developing member 209a, and transferred by a primary transfer voltage to an intermediate transfer belt 200 disposed at a position facing each image forming unit (hereinafter referred to as "primary transfer").

[0071] Similarly, in the image forming units 205b, 205c, and 205d, primary transfer is performed in synchronization with the rotation of the intermediate transfer belt 200 to form a four-color toner composite image. At that time, it is preferable to have one or more metal rollers 212 as primary transfer opposing members between the image forming units 205b and 205c at positions opposing the image forming units via the intermediate transfer belt 200. By forming a primary transfer unit by the metal roller 212 that presses the intermediate transfer belt 200 against the opposing image forming unit, the primary transfer unit width (nip) can be made wide and stable.

[0072] A recording medium 213 such as paper is supplied to a position on the intermediate transfer belt 200 downstream of the position of the fourth image forming unit 205d. A secondary transfer roller 204 (secondary transfer member) is disposed at the same position. The gap formed between the intermediate transfer belt 200 and the secondary transfer roller 204 where the toner image on the intermediate transfer belt 200 is transferred to the recording medium and the vicinity thereof are referred to as the secondary transfer unit. 203 is a tension roller.

[0073] As shown in Fig. 2A, the secondary transfer section is preferably configured to include a nip between a drive roller / secondary transfer opposing roller 201 and a secondary transfer roller 204. When a non-image portion immediately before the toner composite image formed on the intermediate transfer belt 200 reaches the secondary transfer section, a voltage of the opposite polarity to that of the toner is applied from a voltage source 214 that supplies current to the secondary transfer roller 204. Then, when the recording medium 213 passes through the secondary transfer section in the direction of the arrow Vf in Fig. 2A, the four-color toner composite image on the intermediate transfer belt 200 is transferred all at once onto the recording medium 213. This transfer is called "secondary transfer".

[0074] The recording medium 213 on which the secondary transfer has been performed is fixed in a fixing unit (not shown) to become a color image. Meanwhile, toner that has not been secondary transferred and remains on the intermediate transfer belt 200 is scraped off by a cleaning blade 215 that comes into contact with the belt surface on which the tension roller 202 is disposed at any time, and is collected in a waste toner box 216. In this way, the surface of the intermediate transfer belt 200 returns to its initial state.

[0075] The electrophotographic image forming apparatus according to the present disclosure obtains a transfer voltage necessary for the primary transfer as well as a transfer voltage necessary for the secondary transfer from a voltage source 214. The intermediate transfer belt 200 has, for example, a conductive layer on the inner peripheral surface of the belt. The electrophotographic image forming apparatus preferably includes the electrophotographic belt according to the present disclosure as an intermediate transfer belt.

[0076] 2A, the metal roller 212 that contacts the inner circumferential surface of the intermediate transfer belt is connected to a Zener diode 217, which is a constant voltage element, and is grounded. Therefore, the potential of the conductive layer of the intermediate transfer belt is constant in the circumferential direction due to the voltage applied from the voltage source 214. As a result, the potential difference between the photosensitive drum and the intermediate transfer belt in each image forming unit 205a, 205b, 205c, and 205d becomes approximately equal, and the current flowing to each photosensitive drum also becomes approximately equal, enabling primary transfer. Note that since the resistance value of the recording medium itself changes due to environmental fluctuations such as temperature and humidity during image formation, it is preferable to change the secondary transfer voltage within a certain range.

[0077] In the electrophotographic image forming apparatus according to the present disclosure, even if the secondary transfer voltage fluctuates, for example, if the secondary transfer voltage rises, a current flows when the Zener potential is exceeded because the Zener diode 217 is connected. This makes it possible to keep the potential of the conductive layer constant, and to stabilize the primary transferability. Specifically, it is preferable that the applied voltage of the voltage source 214 is 1000 to 3500 V and the Zener potential is 220 to 300 V. According to the present disclosure, by having the above transfer configuration, primary transfer and secondary transfer can be stably performed by one transfer power source.

[0078] According to one aspect of the present disclosure, it is possible to obtain an electrophotographic belt capable of stably forming high-quality electrophotographic images even when applied to an electrophotographic image forming apparatus having a reduced number of power sources for transfer. Also, according to another aspect of the present disclosure, it is possible to obtain an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images even when the number of power sources for transfer is reduced. EXAMPLES

[0079] EXAMPLES The present disclosure will be specifically described below with reference to examples and comparative examples, but the present disclosure is not limited thereto.

[0080] The materials used in the manufacture of the electrophotographic belts according to the examples and comparative examples are shown below. [Table 1]

[0081] The measurement and evaluation methods used in each example are described below. (Evaluation 0) Confirmation of cross-linked polyester urethane in the conductive layer 1720cm attributed to C=O stretching -1 Peaks at 3300-3500 cm due to OH stretching and NH stretching -1 The broad peak at 720 cm, which is assigned to the benzene ring, -1 The presence of a peak in the vicinity was confirmed.

[0082] (Evaluation 1) Confirmation of the presence or absence of aromatic rings (benzene rings), polyester urethane, and triazine rings in the crosslinked polyester urethane in the conductive layer; A 1 cm square sample taken from the conductive layer was measured using a Fourier transform infrared spectrometer (Frontier MIR / NIR+ Spotlight400) (product name, manufactured by PerkinElmer) from 630 to 4000 cm -1 The IR spectrum was measured in the wave number range of 1000 to 2000 nm. The measurement conditions were ATR method (using diamond crystal), measurement area: φ3 mm, wave number resolution: 4 cm -1The number of calculations was 16.

[0083] And from the obtained IR spectrum chart, i) 1720 cm due to C=O stretching -1 Peak of, ii) 3300-3500 cm attributed to OH stretching and NH stretching -1 A broad peak appears in iii) 720 cm assigned to the benzene ring -1 Peaks appearing near iv) 815cm assigned to the triazine ring -1 Peak of, We confirmed whether or not there was any problem. Table 3 shows whether or not each of the peaks related to the above i) to iv) was present.

[0084] (Evaluation 2) Nanoindentation hardness measurement The hardness of the conductive layer was measured using a microindentation hardness tester (Nanoindenter G200, manufactured by Toyo Corporation). The surface of the conductive layer opposite the surface facing the base layer was measured. The measurement temperature was 25°C, and a Berkovich type indenter made of diamond was used as the indenter. The measurement method used was the continuous stiffness measurement method, and the hardness data at a depth of 50 nm from the outer surface of the conductive layer was used for analysis.

[0085] At eight locations in the circumferential direction of the central region of the electrophotographic belt (see FIG. 3), square samples with sides of 5 mm were cut out from the conductive layer with a razor. Each sample was cut out so that one side was parallel to the circumferential direction of the electrophotographic belt. A 2.5 mm square observation area was placed at an arbitrary position on the surface of each sample that corresponds to the outer surface of the conductive layer. The observation area was placed so that one side was parallel to one side of the sample.

[0086] The observation area was divided equally by four lines parallel to one side of the observation area and four lines perpendicular to the lines, and the nanoindentation hardness was measured at 16 intersections of these lines. The arithmetic mean value and standard deviation of the hardness data at the 16 points were obtained, and the coefficient of variation was calculated. The coefficient of variation was calculated by dividing the standard deviation by the average value. The number of samples with a coefficient of variation of 0.25 or less was then determined and listed in Table 3 (the number of observation areas that meet the conditions / 8).

[0087] For Examples 1 to 8 and Reference Example 1, the arithmetic mean value, standard deviation, and coefficient of variation of the observation region with the largest coefficient of variation among the eight observation regions are shown in Table 3. Meanwhile, for Comparative Examples 1 and 2, the mean value, standard deviation, and coefficient of variation of the observation region with the smallest coefficient of variation among the eight observation regions are shown in Table 3. Furthermore, the arithmetic average value of the nanoindentation hardness measured at 128 points from the eight observation regions is shown in Table 3 as the average value of the nanoindentation hardness of the entire conductive layer (overall average value).

[0088] (Evaluation 3) Evaluation of shrinkage rate The shrinkage rate was measured as an index of the shrinkage stress of the electrophotographic belt by the following method. The shrinkage rate was measured using a thermomechanical analyzer (TMA / SDTA841 type, manufactured by Mettler Toledo) under the following measurement conditions, and the change in the chuck distance was measured as the dimensional change of the sample. Sample pieces measuring 5 mm in the circumferential direction of the member x 20 mm in the axial direction and 20 mm in the axial direction of the member x 5 mm in the circumferential direction were cut out from the electrophotographic belt and used.

[0089] The sample piece was held with a chuck distance of 10 mm and a load of 0.01 N, held at 25°C for 10 minutes, heated at 5°C / min to a temperature 10°C higher than the glass transition temperature of the conductive resin composition (crystalline polyester) used in the base layer, held for 30 minutes, and then cooled to 25°C at 5°C / min. The glass transition temperature was measured using a differential scanning calorimeter (DSC3+, manufactured by Mettler Toledo). A 10 mg sample was cut out from the base layer, and the sample was heated from 25°C to 280°C at a heating rate of 10°C / min in a nitrogen atmosphere. In the obtained spectrum, the intermediate temperature between the temperature at which the baseline starts to shift and the temperature at which the baseline shift ends was determined as the glass transition temperature.

[0090] When the chuck distance before the temperature rise was x1 and the chuck distance at the end was x2, the shrinkage rate α (unit: %) was calculated using the following formula. α = (x1-x2) / x1×100 The arithmetic average values ​​were calculated from the measurement results of five sample pieces cut out from the same electrophotographic belt, and the shrinkage rate in the circumferential direction of the electrophotographic belt was designated as αp, and the shrinkage rate in the direction perpendicular to the circumferential direction was designated as αa. The respective values ​​are shown in Table 3.

[0091] (Rating 4) MIT Exam To evaluate durability, an MIT test was performed. A sample was cut from the electrophotographic belt with scissors to have a length of 20 mm in the axial direction and 100 mm in the circumferential direction. This was folded 600,000 times using an MIT type folding endurance tester (No. 307 MIT type folding endurance tester manufactured by Yasuda Seiki Seisakusho Co., Ltd.). The radius of curvature of the clamp was 4 mm, the folding speed was 180 times / min, the folding angle was 135° left and right, and the tensile load was 1 kg. After the MIT test, the folded portion of the conductive layer was observed with a microscope (VHX 100F, manufactured by Keyence Corporation). The presence or absence of cracks of 1 mm or more was confirmed, and the evaluation was made according to the following criteria. Rank A: 0 cracks of 1mm or more Rank B: 1 to 3 cracks of 1 mm or more Rank C: 4 or more cracks of 1 mm or more

[0092] (Rating 5) Image quality rating The obtained electrophotographic belt was used as an intermediate transfer belt of an electrophotographic image forming apparatus having the configuration shown in Figs. 2A and 2B to form an electrophotographic image, and the presence or absence of image defects due to cracks in the conductive layer, which is the inner layer, was confirmed. 2 ) was used, and the print mode was a secondary color image created by superimposing two solid color toner images output in single-sided print mode.

[0093] Here, the secondary color image is an image with an average density of 200% for red (R), green (G), and blue (B). The output image was evaluated according to the following criteria. In addition, after outputting 300,000 sheets, the electrophotographic belt was removed from the electrophotographic image forming apparatus, and the surface of the conductive layer was observed with a loupe at a magnification of 20 times. Then, the presence or absence of cracks in the conductive layer and the output image were evaluated according to the following criteria. Rank A: No image defects occurred during the printing process of 300,000 sheets, and no cracks larger than 1 mm were found. Rank B: No image defects occurred during the printing process of 300,000 sheets, but 1 to 3 cracks of 1 mm or more were confirmed on the edges. Rank C: Defects occurred in the image during the printing process of 300,000 sheets, and four or more cracks of 1 mm or more were found.

[0094] (Measurement of base layer thickness) Using a film thickness gauge (MS-11C, manufactured by Nikon Solutions Co., Ltd.), two measurement points were provided in the axial direction of the electrophotographic belt and four measurement points were provided in the circumferential direction, and the thickness of the base layer was measured. The arithmetic average value of all eight measurement points was calculated and was regarded as the thickness of the base layer.

[0095] [Example 1] <Preparation of paint for forming conductive layer> Vylon UR-1400, used as polyester urethane, contains methyl ethyl ketone as a solvent in addition to the polyester urethane resin component. MHI Black #273, used as a melamine crosslinking agent and conductive agent, and Symac US-270, additive 1, contain isobutanol and methyl ethyl ketone as solvents in addition to the main components melamine crosslinking agent, carbon black, and silicone graft polymer. Meanwhile, ARUFON UC-3000, additive 2, is a solid, so it was dissolved in an equal amount of methyl ethyl ketone as ARUFON UC-3000 before mixing the paint.

[0096] The resin component in the polyester urethane and the melamine crosslinking agent component in the melamine A were mixed so that the mass ratio was 20:9. Additive 1 and Additive 2 were added thereto, and methyl ethyl ketone was added to adjust the viscosity. Furthermore, MHI Black #273 was added as a conductive agent, and the mixture was stirred for 1 hour. The values ​​shown in Table 2 are the masses of the resin components calculated from the masses of the mixed raw materials. The amounts of the conductive agent and additives were adjusted so that carbon black was 23g per 1kg of paint, additive 1 was 2g per 1kg of paint, and additive 2 was 12.5g per 1kg of paint. The amount of methyl ethyl ketone was adjusted so that the total weight of the paint was 1kg.

[0097] <Preform Production> Crystalline polyester (83.7 parts by mass), ionic conductive agent A (1.3 parts by mass), and ionic conductive agent B (15 parts by mass) were hot melt kneaded. Each sample was placed in a twin-screw extruder (product name: TEX30α, manufactured by The Japan Steel Works, Ltd.), and the temperature was adjusted to 270°C and kneaded for 5 minutes. The resulting resin mixture was pelletized.

[0098] The resulting resin mixture was then dried for 6 hours at a temperature of 140° C. A preform was produced from the pellets using an injection molding machine (product name: SE180EV-A, manufactured by Sumitomo Heavy Industries, Ltd.) with a cylinder temperature set to 300° C. The injection mold temperature at this time was set to 30° C. The resulting preform had a test tube shape with an outer diameter of 50 mm, an inner diameter of 46 mm, and a length of 150 mm.

[0099] <Biaxial stretching molding> The obtained preform was placed in a blow molding machine and blow molded in a blow mold maintained at a mold temperature of 110°C using the force of a stretch bar and air at a preform temperature of 155°C, an air pressure of 0.3 MPa, and a stretch bar speed of 1000 mm / s to obtain a blown bottle.

[0100] <Conductive layer formation> The conductive layer forming paint was uniformly sprayed onto the inside of the obtained blow bottle by a spray method, and dried for 5 minutes at 70° C. The amount of paint sprayed was adjusted so that the conductive layer had a thickness of 1 μm.

[0101] <Crosslinking of polyester urethane and melamine crosslinking agent> The blow bottle with the conductive layer formed on the inside was set in a nickel cylindrical mold. An air pressure of 0.1 MPa was applied to the inside of the blow bottle, and the pressure was adjusted so that no air leaked to the outside, so that the blow bottle was tightly attached to the inner surface of the nickel cylindrical mold. Furthermore, while rotating the nickel cylindrical mold, the outer surface of the nickel cylindrical mold was heated to 190°C with a heater, and heated uniformly for a total of 60 seconds, crosslinking the polyester urethane and the melamine crosslinking agent. After that, air at a temperature of 25°C was blown onto the nickel cylindrical mold to cool it to 25°C, and the air pressure applied to the inside of the blow bottle was released. Both ends of the resulting blown bottle were cut by a laser to obtain an electrophotographic belt having a circumference of 630 mm, a width of 250 mm and a thickness of 66 μm.

[0102] [Examples 2 to 5] An electrophotographic belt was produced and evaluated in the same manner as in Example 1, except that the type of melamine crosslinking agent was changed to one shown in Table 2 below.

[0103] [Examples 6 to 7] An electrophotographic belt was produced and evaluated in the same manner as in Example 1, except that the thickness of the base layer was as shown in Table 2 below.

[0104] [Example 8] An electrophotographic belt was produced in the same manner as in Example 1, except that the amount of the melamine crosslinking agent was as shown in Table 2, and evaluated.

[0105] [Reference Example 1, Comparative Examples 1-2] An electrophotographic belt was produced and evaluated in the same manner as in Example 1, except that the material types and blending amounts were as shown in the following Table 2. The evaluation results are shown in Table 3. Reference Example 1 is a case where a melamine crosslinking agent is not included. It is considered that the nanoindentation hardness was lower than that of Example 1 because the crosslinking reaction of polyester urethane did not occur.

[0106] In Comparative Example 1, no pressure was applied when the melamine crosslinking agent and polyester urethane were crosslinked. Therefore, it is considered that the base layer shrunk due to heat during the conductive layer formation process, and a difference in resin density occurred inside the obtained conductive layer, which increased the variation coefficient of nanoindentation hardness. It is considered that the presence of a portion with a large hardness difference in the conductive layer caused cracks in the conductive layer in the MIT test. In Comparative Example 1, the base layer shrunk during the conductive layer formation process, and the evaluation results of the shrinkage rates of αp and αa were 2.0% or less.

[0107] In Comparative Example 2, a base layer having a thickness of 40 μm was used, and no pressure was applied when the crosslinking reaction between the melamine crosslinking agent and the polyester urethane was allowed to proceed. As in Comparative Example 1, the coefficient of variation of the nanoindentation hardness was larger than that in Example 6. This is thought to be the reason why cracks were observed in the observation after the MIT test. The shrinkage rate was also small.

[0108] [Table 2]

[0109] [Table 3]

[0110] The present disclosure relates to the following configurations. (Configuration 1) An electrophotographic belt having an endless shape, The electrophotographic belt has a substrate having an endless shape and a conductive layer in contact with the substrate, The base layer comprises a crystalline polyester, the conductive layer comprises a cross-linked polyester urethane; The crosslinked polyester urethane has a triazine ring in the molecule, When the length in the width direction perpendicular to the circumferential direction of the electrophotographic belt is W, and a region of W / 4 from the midpoint in the width direction toward both ends in the width direction is defined as a central region, an electrophotographic belt, characterized in that, when eight square observation regions, each having a side length of 2.5 mm, are placed in the circumferential direction of the electrophotographic belt in the central region of the outer surface of the conductive layer opposite to the surface facing the base layer, with one side of the square being parallel to the width direction, at least six of the eight observation regions satisfy the following condition: <Condition> The observation area is equally divided by four lines parallel to one side of the observation area and four lines perpendicular to the first lines, and the coefficient of variation of nanoindentation hardness measured at 16 intersections of these lines in an environment of 25°C is 0.25 or less. (Configuration 2) 2. The electrophotographic belt according to configuration 1, wherein the average nanoindentation hardness is 0.15 to 0.30 GPa. (Configuration 3) The electrophotographic belt according to the first or second embodiment, wherein the crosslinked polyester urethane has at least a structure represented by the following formula (1): TIFF2025043155000008.tif63153 In formula (1), R1 to R6 each independently represent is any one selected from the group consisting of a hydrogen atom, -CHOH, -CHOR, and -CHO-, provided that at least two of R to R are -CHO-; R7 is a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms; The symbol "*" indicates a bond to a nitrogen atom that does not constitute a triazine ring in formula (1). The symbol "**" indicates a bond with the polyester urethane in the crosslinked polyester urethane. (Configuration 4) In the structure represented by the formula (1), At least one selected from the group consisting of R1 and R2; At least one selected from the group consisting of R3 and R4; 4. The electrophotographic belt according to claim 3, wherein the compound is -CH2O-**. (Configuration 5) In the structure represented by the formula (1), At least one selected from the group consisting of R1 and R2; At least one selected from the group consisting of R3 and R4; At least one selected from the group consisting of R5 and R6; 4. The electrophotographic belt according to claim 3, wherein the compound is -CH2O-**. (Configuration 6) 6. The electrophotographic belt according to any one of configurations 1 to 5, wherein the crystalline polyester includes at least one selected from the group consisting of polyethylene terephthalate and polyethylene naphthalate. (Configuration 7) 7. The electrophotographic belt according to any one of configurations 1 to 6, wherein the base layer has a thickness of 40 to 100 μm. (Configuration 8) A sample piece cut out from the electrophotographic belt was heated at a rate of 5° C. / min to a temperature 10° C. higher than the glass transition temperature of the crystalline polyester, held for 30 minutes, and then cooled at a rate of 5° C. / min to 25° C., and the shrinkage rate was measured using a thermomechanical analyzer. The electrophotographic belt has a circumferential shrinkage rate αp of 2.0% or more, 8. The electrophotographic belt according to any one of configurations 1 to 7, wherein the electrophotographic belt has a shrinkage rate αa of 2.0% or more in a direction perpendicular to the circumferential direction. (Configuration 9) 9. The electrophotographic belt according to any one of configurations 1 to 8, wherein the conductive layer is present on the inner peripheral surface side of the base layer. . (Configuration 10) 10. The electrophotographic belt according to any one of configurations 1 to 9, wherein the electrophotographic belt is an intermediate transfer belt. (Configuration 11) 11. An electrophotographic image forming apparatus comprising the electrophotographic belt according to any one of Configurations 1 to 10 as an intermediate transfer belt. [Explanation of symbols]

[0111] 100 electrophotographic belt, 101 base layer, 102 conductive layer, 200 intermediate transfer belt, 204 secondary transfer roller, 214 voltage power supply

Claims

1. An electrophotographic belt having an endless shape, The electrophotographic belt has a substrate having an endless shape and a conductive layer in contact with the substrate, The base layer comprises a crystalline polyester, the conductive layer comprises a cross-linked polyester urethane; The crosslinked polyester urethane has a triazine ring in the molecule, When the length in the width direction perpendicular to the circumferential direction of the electrophotographic belt is W, and a region of W / 4 from the midpoint in the width direction to both ends in the width direction is defined as a central region, an electrophotographic belt characterized in that, when eight square observation regions, each having a side length of 2.5 mm, are placed in the circumferential direction of the electrophotographic belt in the central region of the outer surface of the conductive layer opposite to the surface facing the base layer, with one side of the square being parallel to the width direction, at least six of the eight observation regions satisfy the following condition: <Conditions> The observation area is equally divided by four lines parallel to one side of the observation area and four lines perpendicular to the first lines, and the coefficient of variation of nanoindentation hardness measured at 16 intersections of these lines in an environment of 25°C is 0.25 or less.

2. 2. The electrophotographic belt according to claim 1, wherein the average nanoindentation hardness is from 0.15 to 0.30 GPa.

3. 2. The electrophotographic belt according to claim 1, wherein the crosslinked polyester urethane has at least a structure represented by the following formula (1): In formula (1), R1 to R6 each independently represent Hydrogen atom, *-CH 2 OH, *-CH 2 OR7 and *-CH 2 O-**, provided that at least two of R1 to R6 are *-CH 2 O-**, R7 is a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms; The symbol "*" represents a bond to a nitrogen atom in formula (1) that does not constitute a triazine ring. The symbol "**" indicates a bond with polyester urethane in the crosslinked polyester urethane.

4. In the structure represented by the formula (1), At least one selected from the group consisting of R1 and R2; At least one selected from the group consisting of R3 and R4; *-CH 2 4. The electrophotographic belt according to claim 3, which is O-**.

5. In the structure represented by the formula (1), At least one selected from the group consisting of R1 and R2; At least one selected from the group consisting of R3 and R4; At least one selected from the group consisting of R5 and R6; *-CH 2 4. The electrophotographic belt according to claim 3, which is O-**.

6. 2. The electrophotographic belt of claim 1, wherein said crystalline polyester comprises at least one selected from the group consisting of polyethylene terephthalate and polyethylene naphthalate.

7. 2. The electrophotographic belt according to claim 1, wherein the thickness of said base layer is from 40 to 100 μm.

8. A sample piece cut out from the electrophotographic belt was heated at a rate of 5° C. / min to a temperature 10° C. higher than the glass transition temperature of the crystalline polyester, held for 30 minutes, and then cooled at a rate of 5° C. / min to 25° C., and the shrinkage rate was measured using a thermomechanical analyzer. The electrophotographic belt has a circumferential shrinkage rate αp of 2.0% or more, 2. The electrophotographic belt according to claim 1, wherein the electrophotographic belt has a shrinkage rate αa of 2.0% or more in a direction perpendicular to the circumferential direction.

9. 2. The electrophotographic belt of claim 1, wherein said conductive layer is present on the inner peripheral surface side of said base layer. 。

10. 2. The electrophotographic belt of claim 1, wherein the electrophotographic belt is an intermediate transfer belt.

11. 11. An electrophotographic image forming apparatus comprising the electrophotographic belt according to claim 1 as an intermediate transfer belt.

Citation Information

Patent Citations

  • Roll for electrostatic charge and its production

    JP1997211934A

  • Electrophotographic belt and electrophotographic image forming apparatus

    JP2020190720A